2020
DOI: 10.3892/mmr.2020.11101
|View full text |Cite
|
Sign up to set email alerts
|

miR‑96 exerts an oncogenic role in the progression of cervical cancer by targeting CAV‑1

Abstract: cervical cancer is the 4th most common malignant tumor type affecting women worldwide; however, its molecular mechanisms are not fully understood. Previous studies have indicated that micrornas (mirs) serve crucial roles in the cellular functions of tumors. mir-96 is involved in the tumorigenesis of many cancer types. The aim of the present study was to investigate the role and mechanism of mir-96 in the progression of cervical cancer. The present results suggested that overexpression of miR-96 significantly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Many factors contribute to the posttranscriptional regulation of CAV1, such as microRNA (miRNA), long noncoding RNAs (lncRNA), and circular RNA (circRNA), as well as other proteins. Among them, miRNAs, including miR-199a-5p (Zhong et al, 2020), miR-96 (Chen et al, 2020), miR-124 (Torrejón et al, 2017, miR-103/107 (Zhang et al, 2015), miR-204 (Huang et al, 2019), miR-130a (Wang et al, 2016), and miR-103-3p (Wang et al, 2021), have been demonstrated that to recognize homologous CAV1 mRNA and cause the degradation of CAV1 mRNA or inhibit its translation. In addition, lncRNAs, including lncRNA ANRIL (Zhong et al, 2020), lnc-BMP1-1 (Ling et al, 2020), and lncRNA IMFLNC1 , can regulate the protein expression and function of Cav-1.…”
Section: Regulation Of Caveolin-1 Expressionmentioning
confidence: 99%
“…Many factors contribute to the posttranscriptional regulation of CAV1, such as microRNA (miRNA), long noncoding RNAs (lncRNA), and circular RNA (circRNA), as well as other proteins. Among them, miRNAs, including miR-199a-5p (Zhong et al, 2020), miR-96 (Chen et al, 2020), miR-124 (Torrejón et al, 2017, miR-103/107 (Zhang et al, 2015), miR-204 (Huang et al, 2019), miR-130a (Wang et al, 2016), and miR-103-3p (Wang et al, 2021), have been demonstrated that to recognize homologous CAV1 mRNA and cause the degradation of CAV1 mRNA or inhibit its translation. In addition, lncRNAs, including lncRNA ANRIL (Zhong et al, 2020), lnc-BMP1-1 (Ling et al, 2020), and lncRNA IMFLNC1 , can regulate the protein expression and function of Cav-1.…”
Section: Regulation Of Caveolin-1 Expressionmentioning
confidence: 99%
“…Further, qPCR analysis of CAV1gene expression in CESC revealed a significant increase in stage II and an insignificant decrease in stage III than the noncancerous cervical tissue (p-value < 0.05; Figure 3H). A recent study on cervical cancer cell lines has reported the decreased level of CAV1 gene expression, and the miR-96 mediated restoration of the CAV1 has resulted in the decrease of cell proliferation, migration, and invasion 43 . Also, other studies have indicated the tumour suppressor role of CAV1 in various cancers, including cervical cancer [44][45][46] .…”
Section: Epithelial Genes Show a Positive Correlation With Mir34b In Cervical Cancermentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small, non-coding RNA molecules that are associated with the progression of many cancers including CC, serving as tumor promoters or inhibitors [ 11 , 12 ]. For instance, miR-96 served as a tumor promoter in proliferative, migratory and invasive abilities of CC cells by targeting CAV-1 [ 13 ]. While Kan et al found that the miR-1294 level was declined and impeded cell viability and metastasis by interacting with FLOT1 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%